THE INVESTIGATION OF COUNTERMEASURES AGAINST SPACEFLIGHT-INDUCED JOINT DEGRADATION - Patel, Chirayu (Wake Forest University, 2024)
Introduction: The National Aeronautics and Space Administration has outlined a Moon to Mars program with the plan to have long-term manned deep space travel missions outside of low Earth orbit. However, NASA’s Human Research Program has pinpointed five hazards that astronauts will encounter on their journeys, chief among them being space radiation and decreased loadbearing outside of Earth’s gravity. While their effects have been studied in the musculoskeletal and neuromuscular system, it remains relatively unclear as to its effect on joint soft tissue and on neuromotor function. The purpose of this dissertation is to determine if elevated loads applied across the joints of mice aboard the ISS via centrifugation will prevent an OA phenotype and neuromotor deficits in a gravitational load-dependent manner, and if the SOD mimetic MnTnBuOE-2-PyP5+ (BuOE) administration delivered weekly over the course of 35 and 60 days of spaceflight on the ISS will protect against musculoskeletal degradation during and after spaceflight.Research Problem: Does spaceflight environment affect joint health and neuromotor function? What are the health effects of partial gravity environments during spaceflight? Does 1g artificial gravity during spaceflight have protective effects? What is the efficacy of antioxidant pharmaceutical countermeasures for the prevention of spaceflight-induced musculoskeletal degradation? Methods: We performed studies evaluating the efficacy of artificial gravity via centrifugation and antioxidant treatment for the prevention of spaceflight-induced musculoskeletal degradation in rodent models flown aboard the ISS. This study xiii implements microCT to identify morphometric properties, histological, immunohistochemical, transcriptomic, and proteomic analysis to explore potential mechanisms, and gait analysis to characterize neuromotor deficits caused by spaceflight conditions. Conclusions: Treatment with BuOE preserved articular cartilage, menisci, and trabecular bone volume during short duration spaceflight and downregulated pro-arthritic pathways in the joint soft tissue. Exposure to prolonged microgravity aboard the ISS, or partial gravitational loading preserved gait patterns relative to both preflight and controls in a gravity-dose dependent manner. Finally, artificial gravity via centrifugation failed to preserve meniscal volume and articular cartilage thickness, however, 1g AG maintained meniscal ECM synthesis and sulfated GAG expression compared to controls. Future Directions: Further investigation is still needed to validate the protective effects of BuOE on the musculoskeletal system during spaceflight. There is a critical need to characterize these neuromotor deficits in the microgravity and partial gravity environments to better mitigate the risks associated with long-duration spaceflight both in transit and upon reaching a destination, as we plan for missions outside of LEO.
Keywords: Cartilage; Gait; International Space Station; Meniscus; Osteoarthritis; Spaceflight